STRATEGIES IN TEACHING ENGLISH VOCABULARY FOR DEAF STUDENTS IN SLBN SINGKAWANG - Normalita, Devi Tanti; Rosnija, Eni; Sumarni, Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aimed todescribe the strategies used by theteachers in teaching English vocabularyto deaf students atSLBN Singkawang in Academic Year 2021/2022. Theinformant of this research was a teacher from SLBNSingkawang who taught English to deaf students for more than10 years. This research was qualitative descriptive research.The researcher interviewed the teacher and used a semistructured interview about the strategies that had been used toteach English vocabulary to deaf students. The documentsanalysis technique was also used to collect the data. Theresearcher used theory by Miles and Huberman (2014) toanalyze the data. The triangulation technique was used tovalidate the data. The research findings showed that thestrategies used by the teacher to teach English vocabulary todeaf students in SLBN Singkawang were giving the studentsindividualized attention, using visual media, sign language,fingerspelling, and drilling.